2015
DOI: 10.1186/s12955-014-0194-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and early postoperative quality of life after major surgery - a prospective observational study

Abstract: BackgroundChanges in health-related quality of life (HRQoL) several days after surgery have rarely been investigated. We aimed to estimate the perioperative change of HRQoL, to identify patients with clinically relevant decrease in postoperative HRQoL and to establish factors associated with this decrease in HRQoL at day 30 after major surgery.MethodsPatients scheduled for major surgery at a university hospital were enrolled. Based on the HRQoL SF-12 questionnaire, the preoperative physical component summary (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 45 publications
2
27
2
2
Order By: Relevance
“…Those with recent surgical intervention may be stressed and concerned about real tangible issues (such as their leg/chest wounds). Such concern could be addressed using a formalized conceptual coping framework to help the individual cope with immediate stressful issues such as dealing with the surgical wound upon their discharge from hospital (Alkubati et al 2013;Maillard et al 2015;Veronovici et al 2013). This is congruent with several other studies which indicated that patients usually seek information that is more relevant to their current challenging circumstances (Alkubati et al 2013;Kilonzo & O'Connell 2011).…”
Section: Discussionsupporting
confidence: 65%
“…Those with recent surgical intervention may be stressed and concerned about real tangible issues (such as their leg/chest wounds). Such concern could be addressed using a formalized conceptual coping framework to help the individual cope with immediate stressful issues such as dealing with the surgical wound upon their discharge from hospital (Alkubati et al 2013;Maillard et al 2015;Veronovici et al 2013). This is congruent with several other studies which indicated that patients usually seek information that is more relevant to their current challenging circumstances (Alkubati et al 2013;Kilonzo & O'Connell 2011).…”
Section: Discussionsupporting
confidence: 65%
“…Reflecting this inflation in the global assessment, the mean changes in PCS among the “better,” “same,” and “worse” groups (+2.4, −2.4, −7.5) appear to be shifted downward from zero by approximately 2.3 points. Previous studies in unselected surgical populations have also shown no change in VR-12[5] but overwhelming improvement by global assessment [7]. Thus, these results are likely accurate.…”
Section: Discussionmentioning
confidence: 73%
“…17,18 Indeed, QOL after abdominal procedures decreases considerably in the early postoperative phase, and that full recovery is achieved up to 6 months after surgery. 2,4,15,19 …”
Section: Introductionmentioning
confidence: 99%